Perubahan Patologi Seluler Kelenjar Adrenal Tikus Hipertensi dengan Terapi Sel Punca Mesenkimal Sumsum Tulang (CELLULER STUDY OF ADRENAL GLAND IN HYPERTENSIVE RATS WITH IMPACT OF BONE MARROW MESENCHYMAL STEM CELLS THERAPY) - Rumlaklak, Yanse Yanne; Sulistiawati, Erni; Sajuthi, Dondin; Widhyari, Sus Derthi; Nugroho, Setyo Widi (Jurnal Veteriner, 2018)
The purpose of this study was to investigate changes in cellular pathology of adrenal gland as impact of bone marrow mesenchymal stem cells (BMMSC) therapy in hypertensive rats. The research used ten male wistar rats with age ± 10-12 weeks with body weight ± 200-250 grams which is devided into two different groups  ie BMMSc(-) hyprtention and BMMSc(+) hypertension.  Rats are conditioned with hypertention using Hasbinoto et al method. Right nephrectomy and left carotid communic artery ligation are performed on all rats. Rats are injected with deoxycorticosterone acetate (DOCA), then 0.12 % of âaminopropionitrile fumarate (BAPN) is added into drinking water. 1% NaCl solution was administered as drinking water during the study. Rats were evaluated for particular indicator ie blood pressure then were euthanized for adrenal organs collections. The data that obtained then analysed using qualitative descriptive. The result of the study indicate  hypertention therapy using BMMSC can repair cell damaged of the adrenal gland such as hyperplasia, nodules, cysts and cytoplasm vacuolization.